DETERMINATION OF STOCK PRICE VOLATILITY IN CHEMICAL GOODS SUB-SECTOR COMPANIES ON THE INDONESIA STOCK EXCHANGE IN THE 2020-2023 PERIOD - Siti Zahara; Chairil Akhyar; Ristati; Zulfan (PT. Radja Intercontinental Publishing, 2025)
This study aims to analyze the effect of financial and macroeconomic variables on stock price volatility in chemical sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020-2023 period. The population in this study were chemical sub-sector companies listed on the Indonesia Stock Exchange for the 2020-2023 period. The research sample was 15 chemical sub-sector companies obtained using purposive sampling technique. The data collection technique used was documentation. Data analysis was carried out using panel data regression analysis technique using E-views. The results of the study showed that partially the current ratio variable did not have a negative and insignificant effect on stock price volatility. Return on assets, inflation and interest rates did not have a positive and insignificant effect on stock price volatility in chemical sub-sector companies listed on the Indonesia Stock Exchange for the 2020-2023 period.